Assessment of Art Development and Creativity of Children Aged 4-6 Years - Wafa, Lauhani Tsaniyatul; Najiich, Muchammad; Putri, Mita Febrilia; Saripudin, Aip (Al-Mudarris, 2023)
Assessment is important and often necessary in various contexts such as in the development of children's art and creativity. The focus of the assessment is on the artistic development of children aged 4-6. In particular, the researchers looked at and measured how much progress the students had made at the PAUD schools studied, namely RA Al-Hidayah, RA Baiturrahman, and TK PGRI. This research is conducted to understand the extent of artistic development in children aged 4-6 in the PAUD schools under study, with a focus on RA Al-Hidayah, Baiturrahman, and TK PGRI.